KESIAPSIAGAAN PEREMPUAN KAMPUNG PERSAHABATAN INDONESIA-TIONGKOK GAMPONG NEUHEUN KECAMATAN MESJID RAYA ACEH BESAR TERHADAP ANCAMAN BENCANA TANAH LONGSOR - Nova Maulida; Indra .; M. Dirhamsyah (Jurnal Ilmu Kebencanaan : Program Pascasarjana Unsyiah, 2016)
Mesjid Raya is an area that is potentially to landslide or soil movements, particularly at Mesjid Raya Aceh Besar District of Aceh Besar. It is in the yellow zone which is a susceptibilityzone of ground movement, an areas that have a low level of susceptibility of ground motion. This study aims to determine the level of preparedness of women, indicators of preparedness, and the strategy of the women at Kampung Persahabatan Indonesia Tiongkok Desa Neuheun, Mesjid Raya district, Aceh Besar. This study uses a quantitative approach and that is also supported by qualitative. A quantitative approach will be carried out using a questionnaire to obtain the efficient data and qualitative approaches will be implemented using the method of observation, interviews and simulation of landslides. The result showed that women Kampung Persahabatan Indonesia-Tiongkok have not prepared for landslide from education, emergency management, early warning, simulation, preparedness,coordination, risk assessment, information management, resource mobilization